The Right to Seeds and Legal Mobilization for the Protection of Peasant Seed Systems in Mali. (4th February 2021) - Coulibaly, Mohamed; Claeys, Priscilla; Berson, Anne
Abstract: This article discusses the right to seeds and legal mobilization for the protection of peasant seed systems in Mali. It centres on the ongoing 'Seed, Norms and Peasants' process ('Semences, Normes et Paysans', SNP), the goal of which is to achieve the recognition of peasant seed systems in the law. Through the lens of human rights practice, the article explores how peasant organizations and allied NGOs have: a) converged around a shared political agenda despite initial disagreement on the role of certified seeds; b) framed the right to seeds as a collective right, grounded in customary regimes for the governance of land and natural resources; and c) engaged in dialogue with the state to push for legal reform. It further discusses processes of legal transfers and seed aid that have ushered the development of a commercial seed sector in Mali and locates peasant seed systems within the political economy of seeds in the country.